Hydrocinnamic acid produced by Enterobacter xiangfangensis impairs AHL-based quorum sensing and biofilm formation in Pseudomonas aeruginosa. Issue 49 (11th September 2019) - Sharma, Shivangi; Gopu, Venkadesaperumal; Sivasankar, Chandran; Shetty, Prathapkumar Halady
Abstract : Hydrocinnamic acid interacts with LasR receptor averts the autoinducer biding to modulate the expression of quorum sensing mediated phenotypes that strengthens the speculation of hydrocinnamic acid acts as a competitive inhibitor for autoinducer molecule. Abstract : Many of the Gram-negative bacteria regulate their virulence through an AHL-mediated quorum sensing (QS) mechanism. Disruption of this signaling mechanism might be a novel strategy to suppress bacterial virulence. In this report, foodborne bacterial isolates were tested for their QS-inhibitory properties using biosensor strain Chromobacterium violaceum CV026 and the extracted potential active components were evaluated for anti-QS and antibiofilm activity against pathogenic bacteria. The cell-free supernatant of Enterobacter xiangfangensis PUFSTI26 inhibited violacein production in the reporter strain and exhibited a significant reduction in extracellular virulence factors like biofilm formation, pyocyanin production, and motility of Pseudomonas aeruginosa. Characterization of the purified active component by gas chromatography-mass spectrometry (GC-MS) flaunted the resemblance of hydrocinnamic acid (HCA). Treatment of HCA exhibited pronounced attenuation of virulence factors. Further, the biofilm inhibitory activity was evidenced by means of confocal laser microscopy, that evidenced the repression of biofilm biomass. In addition, gene quantification analysis revealed that HCA repressed the expression of major QS-regulated genes. In silico studies showed that HCA competitively interacts with LasR receptor protein. These results clearly indicate the anti-virulence properties of HCA extracted from E. xiangfangensis of food origin. This is also the first report of the QS inhibitor activity of HCA.